Female fetuses are more reactive when mother eats chocolate. (January 2014) - Tranquilli, Andrea L.; Lorenzi, Sara; Buscicchio, Giorgia; Di Tommaso, Mariarosaria; Mazzanti, Laura; Emanuelli, Monica
Abstract Objective: The aim of our study was to analyze whether there is a gender difference in the effects of maternal chocolate ingestion (80% cocoa) on the fetus, as expressed by the fetal heart rate (FHR). Study design: One hundred pregnant women with uncomplicated term gestation, matched for age and parity, underwent computerized FHR recording before and after eating 30 g of 80% cocoa chocolate; 46 carried a male fetus, and 54 carried a female. Computerized cardiotocography parameters (baseline FHR in beats per minute, number of contractions/hour, fetal movements/hour, accelerations of at least 15 bpm for 15 s, episodes of high variation/min and short-term variation in ms) were expressed as the mean and SD. We calculated the difference before and after maternal chocolate eating both in male and female fetuses and then compared the gender differences in the FHR variation. Statistical significance was set at p < 0.05. Results: While baseline FHR and number of contractions did not change, the number of: fetal movements/hour, accelerations, episodes of high variation/min, and the short-term variation significantly increased after chocolate ingestion. The percent variation of the movements (101.7 ± 89.23 males versus 252.0 ± 297.6 females; p = 0.002), accelerations (70.90 ± 46.98 males versus 153.3 ± 178.5 females; p = 0.004) and short-term FHR variation (21.47 ± 18.73 males versus 37.35 ± 27.46 females; p = 0.002) increased to a greater degree in the female fetuses than in the males. Conclusions: The maternal ingestion of dark chocolate induces much more reactivity in female fetuses than in males. This finding supports the existence of an innate gender difference for the effects of chocolate, present even since the fetal period.